Shielding features of concrete types containing sepiolite mineral: comprehensive study on experimental, XCOM and MCNPX results - Sayyed, M. I.; Tekin, H. O.; Kılıcoglu, O.; Agar, O.; Mohd Zaid, Mohd Hafiz (Elsevier, 2018)
Natural sepiolite mineral is a naturally occurring clay form belonging to a part of layered silicate. Because of its advantages such as low production cost, light-weight and convenient, it may be selected as an alternative shielding material to others. Radiation shielding performances of some concretes to sepiolite and B4C addictive have been researched reported in a wide energy region of 0.08–1.333 MeV using experimental data, MCNP and XCOM. The simulated data obtained by MCNPX are discussed and compared with the experimental results as well as with the XCOM results. The simulations match the experiments very well except for S3 sample. From the measurement, the maximum gamma-ray attenuation was detected in the concrete specimen with 10% sepiolite (S1) while the minimum attenuation of gamma-ray was noted in the concrete specimen with 30% sepiolite (S3). The addition of sepiolite mineral to concretes may be an alternative option that can be used in several radiation protection applications.